Spiritualitas Menurut Yohanes Calvin dan Implikasinya bagi Pendidikan Warga Gereja di Era New Normal - Agustina Pasang (Institut Agama Kristen Negeri Toraja, 2020)
Abstract: One of the spiritualities that is important to learn and understand is spirituality according to John Calvin, which emphasizes the importance of the principle regarding the relationship between humans and God. Deeper recognition gives an indication that a person’s relationship with God is getting closer and closer to God, which will have an impact on spiritual growth. However, the spiritual understanding that is widely discussed today does not always originate from the existence of God but also from the potential of the human self. The purpose of this paper is to understand spirituality according to Calvin so that it can be a reference for the education of church members in the new normal era. This research uses a descriptive research method with a literature review approach and field data collection at the Indonesian Evangelical Mission Alliance Church in Balikpapan. Spirituality according to Calvin, if properly understood can help church members to have a correct understanding of knowing God and realizing the importance of spiritual growth and can find the strength to continue to grow in a stronger spiritual life that is expressed in the attitude of each individual’s life. Abstrak: Salah satu spiritualitas yang penting untuk dipelajari dan dipahami adalah spiritualitas menurut Yohanes Calvin, menegaskan pentingnya relasi antara manusia dengan Allah. Pengenalan yang semakin dalam memberi indikasi semakin erat dan intimnya relasi seseorang dengan Allah yang berdampak pada pertumbuhan spiritualitas. Namun pemahaman spiritual yang ramai dibicarakan saat ini tidak selalu bertolak dari keberadaan Allah tetapi juga dari potensi diri manusia. Tujuan dari penulisan ini adalah untuk memahami spiritualitas menurut Calvin, supaya dapat menjadi acuan bagi pendidikan warga gereja di era new normal. Adapun penelitian ini menggunakan metode penelitian deskriptif dengan pendekatan kajian literatur dan pengumpulan data lapangan di Gereja Persekutuan Misi Injili Indonesia (GPMII) Balikpapan. Spiritualitas menurut Calvin, jika dipahami secara benar dapat menolong warga gereja untuk memiliki pemahaman yang benar mengenai pengenalan akan Allah serta menyadari pentingnya pertumbuhan spiritualitas dan dapat menemukan kekuatan untuk terus bertumbuh dalam kehidupan spiritualitas yang lebih kokoh yang dinyatakan dalam sikap hidup tiap hari